PENGARUH PAJAK DAERAH DAN RETRIBUSI TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI SUMATERA UTARA - Rizqy Ramadhan, Puja (Universitas Medan Area, 2019)
This study is objected to find out and analyze the effect of local taxes on districts/cities regional revenue in North Sumatra; to find out and analyze the effect of regional retribution on districts/cities regional revenue in North Sumatra; and to find out and analyze the effect of regional taxes and regional retribution simultaneously on regional revenues in districts/cities in North Sumatra. The population in this study is audited financial statements in all districts/cities government in North Sumatra, which 33 districts/cities in the period 2016, 2017 and 2018. The samples were selected using the census method. Data is processed using multiple linear regression statistical test methods. The results of this study proved the local taxes affect the district/cities regional revenue in North Sumatra. Therefore, the regional retribution and regional have a simultaneous effect on on regional revenues in districts/cities regional revenue North Sumatera.